Crystallization Phenomenon in Defective Goethites - Canetti de las Cuevas, Dora; Correa Reina, José Raúl; Llópiz Yurell, Julio César (Ciencia, 1970)
Samples of iron oxihydroxides were synthesized from Fe2(SO4)3 and NaOH at room temperature followed by steam treatment in 1 M KOH for several intervals of time. The crystallinity variation of the goethite in function of ageing was studied by means of Infrared Spectroscopy, XRD and DTA. The product of dehydration, Fe2O3, maintains the defect structure up to a temperature between 580 to 725°C where an exothermic effect is observed in the DTA due to stress relief and recrystallization